Policing the Virtual Border: Punitive Preemption in Australian Offshore Migration Control - Weber, Leanne (Social justice, 2007)
Part of a special issue on the role of criminal organizations and individuals, and that of political states and their economic partners in transnational crime. A study was conducted to examine punitive preemption in Australian off-shore migration control. Data were obtained from a review of the literature and government documents concerning three aspects of this phenomenon: interceptions of “inadequately documented” travelers by liaison officers in countries of transit; military interdiction of “suspected unlawful non-citizens” at sea; and the manipulation of the location of borders to preempt the arrival of “off-shore entry persons”. Findings revealed that these cases of Australian preemptive migration policing demonstrate a variety of punitive, militaristic, and regulatory practices operating within a “nebulous zone of preemptive action.” Findings suggested that all of these raise concerns about the exercise of authority without responsibility in uncharted zones of questionable legal authority. Findings are discussed in detail.